2013
DOI: 10.4049/jimmunol.1203045
|View full text |Cite
|
Sign up to set email alerts
|

Location of CD4+ T Cell Priming Regulates the Differentiation of Th1 and Th17 Cells and Their Contribution to Arthritis

Abstract: T helper (Th) cytokines IFN-γ and IL-17 are linked to the development of autoimmune disease. In models of rheumatoid arthritis (RA) i.e. proteoglycan (PG) -induced arthritis (PGIA), IFN-γ is required whereas in collagen-induced arthritis, IL-17 is necessary for development of arthritis. Here we show that the route of immunization determines the requirement for either IFN-γ or IL-17 in arthritis. Intraperitoneal (i.p.) immunization with PG induces a CD4+ T cell IFN-γ response with little IL-17 in the spleen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…IL-17 is a potent pro-inflammatory cytokine produced by activated T cells, particularly Th17 cells, and has been associated with pathogenesis of a wide range of inflammatory and autoimmune diseases including SLE and RA (Miossec and Kolls, 2012; Nalbandian et al, 2009; Rodeghero et al, 2013). To investigate the impact of NAC supplementation on TCE-mediated IL-17 release, splenocytes isolated from control, TCE alone, NAC alone or TCE + NAC-treated mice were cultured with or without ConA or anti-mouse CD3/CD28, and the release of IL-17 into the culture supernatants was determined.…”
Section: Resultsmentioning
confidence: 99%
“…IL-17 is a potent pro-inflammatory cytokine produced by activated T cells, particularly Th17 cells, and has been associated with pathogenesis of a wide range of inflammatory and autoimmune diseases including SLE and RA (Miossec and Kolls, 2012; Nalbandian et al, 2009; Rodeghero et al, 2013). To investigate the impact of NAC supplementation on TCE-mediated IL-17 release, splenocytes isolated from control, TCE alone, NAC alone or TCE + NAC-treated mice were cultured with or without ConA or anti-mouse CD3/CD28, and the release of IL-17 into the culture supernatants was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Although disease severity (arthritic index and histopathology), the presence of spondylitis, and even serum factors such as RF and anti-PG antibodies are similar, the dominant cytokines indicative of a Th1 or Th17 response differ depending on the route of immunization (intraperitoneal vs intradermal) used for arthritis induction [63]. The potential for Th1 or Th17 signature phenotypes in the same animal model has also been noted for animal models of MS [64] and uveitis [65].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…RA has been regarded as a classic T cell-mediated chronic inflammatory autoimmune disease for years. Abnormal activation of T cells in RA are the main induced factors causing immune damage and synovial pathologic histology change (Alzabin and Williams, 2011;Rodeghero et al, 2013). In our previous study, we found that CK alleviated CIA and adjuvant-induced arthritis, downregulated the percentage of activated T cells, and upregulated naive T cells and regulatory T cells (Tregs) in spleen Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The excessive activation of T cells causes undesirable immune responses against self-antigens, which then results in chronic inflammatory and autoimmune response (Pablos and Cañete, 2013;Rodeghero et al, 2013). In our previous study, a decreased percentage of naive T cells, a raised percentage of activated T cells, and hyperplasia of T cells were observed in autoimmune arthritis animal models (Chang et al, 2011;Liu et al, 2011;Song et al, 2013;Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%